Are Bacterial Persisters Dormant Cells Only? - Zou, Jin; Peng, Bo; Qu, Jiuxin; Zheng, Jun (Frontiers in Microbiology, 2022)
Bacterial persisters are a sub-population of phenotypic variants that tolerate high concentrations of antibiotics within the genetically homogeneous cells. They resume division upon the removal of drugs. Bacterial persistence is one of major causes of antibiotic treatment failure and recurrent infection. Cell dormancy, triggered by toxin/antitoxin pair, (p)ppGpp, SOS response and ATP levels, is known to be the mechanistic basis for persistence. However, recent studies have demonstrated that bacteria with active metabolism can maintain persistence by lowering intracellular antibiotic concentration via an efflux pump. Additionally, others and our work have showed that cell wall deficient bacteria (CWDB), including both L-form and spheroplasts that produced by β-lactam antibiotics, are associated with antibiotic persistence. They are not dormant cells as their cell walls have been completely damaged. In this review, we discuss the various types of persisters and highlight the contribution of non-walled bacteria on bacterial persistence.